2007
DOI: 10.1016/j.febslet.2007.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the deficiency of the rhodanese‐like protein RhdA in Azotobacter vinelandii

Abstract: In Azotobacter vinelandii the rhdA gene codes for a protein (RhdA) of the rhodanese-homology superfamily. By combining proteomics, enzymic profiles and ultrastructural observations, the phenotype of an A. vinelandii rhdA mutant was analyzed. We found that the A. vinelandii rhdA mutant, and not the wild-type strain, accumulated polyhydroxybutyrate. RhdA deficiency enhanced the expression of enzymes of the polyhydroxybutyrate biosynthetic operon, and affected the activity of specific tricarboxylic acid cycle enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 39 publications
3
27
0
Order By: Relevance
“…The phenotypic characterization of the A. vinelandii rhdA mutant strain MV474 (Cereda et al, 2007(Cereda et al, , 2009 clearly showed that inactivation of enzymes containing labile Fe-S clusters (Imlay, 2006) was enhanced in the absence of RhdA. Our goal was, therefore, to explore whether these effects could correlate with an altered redox balance in A. vinelandii cells lacking RhdA.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The phenotypic characterization of the A. vinelandii rhdA mutant strain MV474 (Cereda et al, 2007(Cereda et al, , 2009 clearly showed that inactivation of enzymes containing labile Fe-S clusters (Imlay, 2006) was enhanced in the absence of RhdA. Our goal was, therefore, to explore whether these effects could correlate with an altered redox balance in A. vinelandii cells lacking RhdA.…”
Section: Resultsmentioning
confidence: 99%
“…The first indication that RhdA could protect A. vinelandii from oxidative events stemmed from the observation that in the presence of the superoxide generator PMS, A. vinelandii growth was significantly impaired only in the rhdA mutant strain (Cereda et al, 2007(Cereda et al, , 2009 highlight whether the presence of RhdA could buffer the effects of oxidative stress.…”
Section: Protective Action Of Rhda Against the Superoxide Generator Pmsmentioning
confidence: 99%
See 3 more Smart Citations